Middle School Teachers’ Professionalism (Beliefs and Attitudes) Toward Technology in Developing 3D Videos Using Plotagon - Harisman, Yulyanti; Resmi Darni; Nadiyatul Ghina; Hafizatunnisa; Minora Longgom Nasution; Fitrani Dwina; Pipin Sumarni; Mazlini Adnan (Rangkiang Mathematics Journal, 2025)
This study focuses on the professionalism of teachers, particularly in terms of their attitudes and beliefs toward the integration of digital technology in teaching and learning activities. Plotagon was selected as a medium for developing interactive and contextual 3D instructional videos. The research employed a survey method aimed at exploring teachers’ interest in and acceptance of Plotagon as a supportive tool for instructional materials. The participants comprised twenty-eight junior high school teachers in Sawahlunto City. Prior to the survey, the teachers received intensive training on creating instructional videos using Plotagon. Data were collected through direct observation, questionnaires, and structured interviews. The findings reveal that the majority of teachers (91%) demonstrated positive beliefs regarding the use of digital culture-based technology through Plotagon, while 88% considered the medium beneficial for students. Furthermore, 86% of teachers showed high levels of engagement, and an equal proportion actively participated throughout the implementation process. These results imply that integrating digital storytelling platforms such as Plotagon can enhance teachers’ professional competence and foster innovative teaching practices.